Development of underground wireless SAW integrated sensor measurement system using magnetic field - Kim, Sihyeok; Lee, Keekeun (Transactions of the Korean Institute of Electrical Engineers, 2020)
A wireless underground sensor system was developed based on magnetic antennas and SAW sensor. The developed sensor system can wirelessly detect the ambient temperature, humidity, and hydrogen gas leakage in buried utilities up to about ~1m in underground. By using SAW sensors with different resonance frequencies, it is also possible to analyze information from different locations in underground using one antenna which is located on the ground. A 260~300 MHz magnetic antenna generated a surface acoustic wave along the piezoelectric substrate, and the returned SAW energy from the reflection bars were reconverted to magnetic flux via the sensor's interdigital transducer (IDT) and subsequently transmitted to a reader in upperground. The developed system showed stable performance regardless of underground media (water, air, soil). Sensitivity and linearity for the temperature sensor was 5.06 °/°C and 0.98 respectively. Sensitivity and linearity for the gas sensor was 1.1 °/ppm and 0.96 respectively. It was analyzed that the humidity sensor has 6 °/RH% sensitivity and 0.95 linearity.
Keywords: Buried utilities; Integrated sensors; Interdigital transducer; Magnetic antennas; Piezoelectric substrates; Resonance frequencies; Stable performance; Surface acoustic waves; Humidity sensor; Hydrogen sensor; Interdigital transducer (IDT); Magnetic antenna; Surface acoustic wave (SAW); Temperature sensor; Underground wireless communication